Tribes and Trafficking: Trans-Saharan Illegal Trade Routes as a Conflict Factor in the Sahara-Sahel Region - G. V. Lukyanov; A. M. Nadzharov (Международная аналитика, 2025)
The conflict in the Sahel that began in 2012 is closely linked to the phenomenon of trans-Saharan illicit trade routes through Mali, Niger and Libya. These routes represent a type of trans-Saharan trade currently composed of a set of traffic: drug traffic, migrant traffic, and traffic in illegally mined gold. This article examines the factor of these flows in the conflict political economy of the Sahel. It is argued that the emergence and intensification of these flows have intensified inter- and intra-ethnic tensions between the main tribes involved in this trade: the Tuareg, Arabs, and Toubou. Using theoretical and methodological insights from the political economy of conflict, the authors show that these flows not only supported the activities of armed ethnic groups, but were themselves an opportunity for traditionally marginalized groups to redefine their position in the socio-economic hierarchy. The article analyzes this phenomenon through the case studies of three interconnected regions: northern Mali (Azawad), northern Niger (Agadez), and southwestern Libya (Fessan). The article also examines the evolution of the geographical routes of illegal flows and the strategies of state actors to co-opt them. The authors conclude that these flows are central not only to the political economy of conflict in the Sahel, but also to the economies of desert regions in general, suggesting the sustainability of the phenomenon of trans-Saharan illicit trade.